Payback time? Discourses of lack, debt and the moral regulation of teacher education. Issue 1 (2nd January 2016) - Beighton, Chris
Abstract : This paper analyses recent policy and discourse in the UK lifelong learning sector to identify a tension in discourse which positions teacher educators as essential to the knowledge economy while simultaneously insisting on the deficits they represent. Drawing on critical analyses from Friedrich Nietzsche, Maurizio Lazzarato and Gilles Deleuze, I challenge altruistic views of professional motivation and situate individual professionalism under a construction of an indebted subject. Examining recent attempts to redefine professional standards in the sector, I argue that teachers are positioned as subject to homogenisation and ethically indebted to a higher ideal. Ethical commitments to adult learning, I suggest, are a cost-effective instrument of social control because of their imbrication in this discourse of irredeemable moral debt to the sector. Responses to this situation, I argue, are likely to include forms of professional mobility which undermine it.